(3ef GdeZQH Edi GdMLGR YHQ ChQhHG (B1857 /s - (3GdZjZGFj, eMeO Hf YHO Gddg Hf eHGQcs (3bQf (B13 (3gLQjs; (3GdbQTj, SdjeGfs 1969- ((3HjQhJ (B- (3dHfGf (B:s (3GdeDSSI GdYQHjI ddOQGSGJ hGdfTQ ,s (3CHhXHj (B- (3GdEeGQGJ GdYQHjI GdeJMOI (B:s (3OGQ GdShjOj ddfTQ hGdJhRjY,s (3YqeGf GdCQOf (B:s (3OGQ GdaGQS ddfTQ hGdJhRjY ,s, 2018)
(3gPG GdcJGH gh jhejGJ QMdI MLjI aQjOI JfJej Edi GdbQf Gd` (B19(3, bGe UGMHgG GdZjZGFj HgG aj ChGSW TgQ TYHGf ef SfI (B1857 (3hGSJeQJ JSYI CTgQ(B. (3hcGf efWdbg ef eOjfI eQGcT YHQ GdUhjQI aWfLI GdJj ZGOQgG Ydi XgQ SajfI JLGQjI aj GJLGg LHd WGQb, Ke LRjQI eGdWI aeUQ YHQ HhGHI GdEScfOQjI, hbO fGdJ eUQ fUjH GdCSO ef GdSQO hGdhUa HGYJHGQ ecGfJgG GdegeI dOi GdQMGdI GdeZGQHI(B. (3aj gPg GdjhejGJ jJLdi GdLGfH GdPGJj aj JYHjQ GdQMGdI GdeZQHj Yf dhGYLg hCMGSjSg fMh CbOS GdCeGcf GdESdGejI(B. (3CeG GdYGed GdehVhYj Nda GdGSJaGVI aj hUagG, hSQO CMhGd GdEbGeI aj ecI, agh VQhQI GdJYQja HGdefGSc hHaVGFd GdHjJ, agj JVWdY HhGLH JYdjej(B. (3haj GdeOjfI GdefhQI jMVQ GdLGfH GdQhMj hGdhLOGfj, hJJcKa GdCMGSjS hJJRGMe GdYHGQGJ dGSjeG dOi Gdhbha Ydi GdbHQ GdfHhj GdeHGQc, hgh aj QMdGJ GdeZGQHI jSJOYj bUGFO GdeOjM(B.s
.(3GdcJGH GdMGFR Ydi LGFRI GHf HWhWI dJMbjb GdeNWhWGJ (B2017 - 2018s
(3JUeje GdZdGa (B: (3fGUQ HNjJ ; GdUa GdVhFj (B: (3GdeDSSI GdYQHjI ddOQGSGJ hGdfTQ(B.s
(3edGMb (B: (3UaMI (B225-234s
(3HHdjhLQGajI (B: (3UaMI (B235.s
Keywords: (3GdMLs; (3ecI GdecQeIs -- (3hUa hQMdGJs; (3GdeOjfI GdefhQIs -- (3hUa hQMdGJs; (3GdeZQHs -- (3hUa hQMdGJs; (3GdMLGR (B((3GdSYhOjI(B)s -- (3hUa hQMdGJs